Factors Predicting Treatment Adherence Among Patients with Hypertension: A Systematic Review and Meta-Analysis - Win, Thandar; Thanaslip, Sureeporn; Polsook, Rapin (National Journal of Community Medicine, 2025)
Background: Through the increased prevalence of hypertension, the notch of following the prescribed anti-hypertensive treatment among these populations is very inadequate, and the unsatisfactory disease control rate. This study systematically reviewed and identified their characteristics of the predicting factors on it and their magnitude. Methodology: By the Joanna Briggs Institute (JBI) methodology, the included articles were critically appraised and assessed their certainty of evidence with the GRADE guidelines. Four databases (Google Scholar, ScienceDirect, PubMed, and WILEY online) and the keywords of treatment adherence” OR “compliance” AND “determinants” OR "factors" OR "predictors" OR “influences” AND "hypertension" OR “high blood pressure” were applied. The integrated effect sizes (z), 95% confidence intervals (CIs), and I2 index were reported. Findings: Descriptive correlational and longitudinal designs were included in total 20 studies. The significant predictors were demographic, intrapersonal, interpersonal, condition-related, and health system-related ones. Patients’ self-efficacy, perception, co-morbidity and social support produced the most significant effects. Additionally, various adherence levels to treatment were reported as low to acceptable. Conclusion: The hypertension society should strengthen their adherence practices by clear instructions and guidance, especially for multimorbid ones, by improving their self-efficacy and perception on their disease, building social support and virtuous patient-provider communication.